Al-Af’āl Al-Ṡulātsiyyah Al-Mazidati Wa Ma’ānīhaa Fī Kitābi Matani Safīnati An-Najāh - Ahmad Hidayatullah Zarkasyi; Julisal Farah (Department of Arabic Teaching, Faculty Tarbiyah, Universitas Darussalam Gontor, 2020)
Sorof is one of the inseparable parts in Arabic, where Arabic itself is famous for us, its rich meaning and meaning implicit in it. With Sorof, we can understand the change of meaning from one word to another. If we do not pay attention to it, there is a wrong understanding of the meaning after the change in the sentence. As is, well known that each bina al-fi’li has its own meaning and usefulness in siyaqul kalam, examples of afazala wazan are more biased in terms of takdiyah, and wazan infa’ala is more biased in meaning for muthowa’ah. Therefore the researcher will examine the features of the mazid sulation and its meaning in the book of matan safinah najah, where the safinah book itself has many meanings implied in it and this book is very much needed for the community to understand daily worship. From the results of the study found: (1) fi sulation of mazid in the book of matan safinah as many as 91 sighoh, consisting of a one letter affix with 57 words and a two letter affix there are 30 words and a three letter affix there are 4 words. (2) The meanings of the formulation of mazid contained in the book are: attakdiyah, shirurah, musyarakoh, mothowaah, tadahur and ittihad.